2013
DOI: 10.1039/c3dt50698c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a tetrathiafulvalene-salphen actinide complex

Abstract: A new tetrathiafulvalene-salphen uranyl complex has been prepared. The system was designed to study the electronic coupling between actinides and a redox active ligand framework. Theoretical and experimental methods -including DFT calculations, single crystal X-ray analysis, cyclic voltammetry, NMR and IR spectroscopies -were used to characterize this new uranyl complex.A large number of complexes based on organic donor tetrathiafulvalene (TTF) ligands and 3d transition metal centers are known. 1 Complementing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…1 This has made TTF and its derivatives attractive for use in a wide range of applications, including molecular-based electronics and optoelectronics. 2 As a result, TTF has been incorporated into a variety of molecular scaffolds and ensembles, which have been exploited inter alia as receptors for electron deficient guests, 3 redox active ligands 4 and molecular machines. 5 Moreover, Misaki and coworkers 6 suggested that grafting TTF subunits onto a p-conjugated platform could provide an approach to developing high charge storage capacitors and molecular batteries.…”
mentioning
confidence: 99%
“…1 This has made TTF and its derivatives attractive for use in a wide range of applications, including molecular-based electronics and optoelectronics. 2 As a result, TTF has been incorporated into a variety of molecular scaffolds and ensembles, which have been exploited inter alia as receptors for electron deficient guests, 3 redox active ligands 4 and molecular machines. 5 Moreover, Misaki and coworkers 6 suggested that grafting TTF subunits onto a p-conjugated platform could provide an approach to developing high charge storage capacitors and molecular batteries.…”
mentioning
confidence: 99%
“…[18] of this article for further details). Likewise, oxidation of a series of uranyl‐salophen complexes have recently been determined to form ligand radical compounds, and a tetrathiafulvalene‐salphen uranyl complex has been confirmed by theory and experiment to produce radical species during oxidation of the complex . Although in certain cases oxidation of uranyl(VI) compounds has resulted in oxidation of the coordinating ligand and produced radical species, these may not always undergo or induce further chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, oxidation of a series of uranyl-salophen complexes have recently been determined to form ligand radical compounds, [27] and a tetrathiafulvalenesalphen uranyl complex has been confirmed by theory and experiment to produce radical species during oxidation of the complex. [28] Although in certain cases oxidation of uranyl(VI) compounds has resulted in oxidation of the coordinating ligand and produced radical species, these may not always undergo or induce further chemical transformations. However, electrochemical oxidation of the uranyl penta-thiocyanate ([UO 2 (NCS) 5 ] 3À ) complex results in oxidation of thiocyanate ligands and triggers a subsequently unprecedented uranyl(VI) reduction.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In contrast, the uranyl(VI) α-di-imine diphenolate ( 1 ) ( Figure 1 ) and uranyl(VI) salophens undergo one-electron reduction of the ligand, leading to ligand-centered radical anions and not the expected uranyl(V) complexes. 9 , 10 , 17 …”
Section: Introductionmentioning
confidence: 99%